Upaya Pencegahan COVID-19 melalui Peningkatan Pengetahuan Ibu mengenai PHBS di Lingkungan Keluarga pada Masa Pandemi - Vidya Nursolihati; Annisaa Putri Ariyani; Lies Zubardiah; Alfred Pakpahan; Iqbal Zein Assyidiqie (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Until now, there is still no specific treatment that has proven effective for COVID-19, so prevention of the disease is the best way to break the chain of its transmission. This prevention effort requires participation from the entire community. However, it is not easy for people to participate due to a lack of understanding about the disease and awareness of clean-living behavior to prevent infection. Yayasan Rumah Ibu Indonesia (Rumaisa) is a foundation that focuses on increasing family resilience. One of the targets for clean and healthy living behavior (PHBS) is household/family; therefore, PHBS education and training in homes during the pandemic, especially for mothers, is a strategic way to mobilize and empower family members to practice clean and healthy behavior. This study aims to determine the effect of education and training of PHBS within families during the pandemic on mothers’’ knowledge in Yayasan Rumaisa. Participants’ level of knowledge is measured using a questionnaire given before and after the education and training, in the form of pre-test and post-test. From the results, it can be seen that the post-test scores were increased compared to the pre-test scores. An increase in participants’ knowledge of PHBS within families during the pandemic is expected to increase community participation in preventing disease transmission, especially COVID-19.